2006
DOI: 10.1111/j.1440-1746.2005.04146.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fibrosis in Asian patients with non‐alcoholic steatohepatitis

Abstract: Septal fibrosis is common in Asians with NASH. Necroinflammatory grade >or= 2, AST >or= 2 x ULN and DM are independent predictors for septal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
4
22
1
1
Order By: Relevance
“…The prevalence of advanced fibrosis in our cohort was only 2.98%. This proportion is smaller than that reported by other Asian studies, 32,33 which would tend to increase the NPV of the noninvasive fibrosis scoring systems examined in the present study. This divergence may have been caused by the low mean BMI of our patients, which was <25 kg/m 2 in 67.2% of our cohort.…”
Section: Patient Characteristicscontrasting
confidence: 82%
“…The prevalence of advanced fibrosis in our cohort was only 2.98%. This proportion is smaller than that reported by other Asian studies, 32,33 which would tend to increase the NPV of the noninvasive fibrosis scoring systems examined in the present study. This divergence may have been caused by the low mean BMI of our patients, which was <25 kg/m 2 in 67.2% of our cohort.…”
Section: Patient Characteristicscontrasting
confidence: 82%
“…The incidence is markedly higher than the 20.3% incidence observed in patients with NAFLD (Gramlich et al, 2004) but is comparable with that found in Northern European young adult alcoholics (38.9%-73.7%; Savolainen et al, 1995), as well as in young Asian adults (57%) with NASH (Tsang et al, 2006). Thus, perisinusoidal fibrosis seems to occur as frequently in older adult cadavers with diverse causes of death as in young adult alcoholics and NASH patients.…”
Section: Discussionsupporting
confidence: 65%
“…We found bridging fibrosis in 30.8% of the elderly cadaveric livers. This incidence is higher than the 10% incidence observed in Asian young adults with NASH or 14.4 % (septal/bridging fibrosis combined) in NAFLD patients, as assessed by histopathology (Gramlich et al, 2004;Tsang et al, 2006). It is also markedly higher than the 2.8% bridging fibrosis reported in French young adults or 6% in European young adult HCV patients coinfected with HIV, as estimated by FibroTest V R (Martín-Carbonero et al, 2009;Poynard et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Among nearly 1000 morbidly obese subjects undergoing gastrointestinal bariatric surgery in Italy, an aspartate aminotransferase (AST) or ALT level greater than twice the upper limit of normal had a positive predictive value (PPV) for bridging fibrosis of 21% and a negative predictive value (NPV) of 93% [36]. An AST greater than twice the upper limit of normal was also independently predictive of portal or bridging fibrosis in an Asian study of 60 patients with NAFLD [37]. However, other studies have failed to confirm an association between simple aminotransferase levels and degree of fibrosis in patients who have NAFLD [3840].…”
Section: Serum Markers Of Liver Fibrosis In Nashmentioning
confidence: 99%